Recenzja książki: "Errando discimus?" – O pewnej gramatyce języka łacińskiego - Pieczonka, Joanna (Collectanea Philologica, 2021)
The article concerns the Latin Grammar by Emilia Kubicka, published in 2019. The book presents the rules of the Latin pronunciation, conjugation, declension of the nouns, adjectives, numerals, pronouns, and the indeclinable parts of speech such as adverbs and prepositions. However, the grammar does not present all the principles that govern the structure of Latin sentences, and the book has numerous errors.